Pengaruh Kualitas Audit dan Auditor Switching Terhadap Manajemen Laba - Felita Icasia Hadi; Sherly Tifani (P4M STIE Putra Bangsa, 2020)
The purpose of this study is to examine the effect of audit quality and auditor switching on earnings management with the audit fee as the intervening variable. Data in this study is secondary data derived from the annual report of listed companies in Indonesia Stock Exchange in 2016-2018. There are 117 samples and the method used for sampling is purposive sampling. The hypothesis in this study was tested using multiple regression. The result of this study showed that audit quality positively influences fee audit but not significant, auditor switching negatively influence fee audit, audit quality influence earnings management with negative direction, auditor switching positively influence earnings management but not significant, fee audit negatively influence earnings management but not significant, and there is no influence of intervening variable in the relationship between audit quality and auditor switching on earnings management.